1981
DOI: 10.1037/h0077752
|View full text |Cite
|
Sign up to set email alerts
|

Development of sociosexual approach behavior in male laboratory rats.

Abstract: Approach behavior toward male and female incentives was studied in male laboratory rats during development from prepuberty to adulthood. Both incentives were approached, but the magnitude of the response changed with age. At 70 days of age, the typical adult approach response was evident: The female was contacted for the better part of a session, and the male incentive was contacted very little. The time for the appearance of this contact response was not obviously influenced by prepuberal experience in intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…In order to mimic the physiological process of sexual maturation, testosterone replacement therapy was initiated approximately at the age at which the testes first start secreting high concentrations of androgens (Ottinger and Brinkley, 1979). Studies conducted in young rats and zebra finches revealed that the amount of time males spend looking at females as compared to males, family members or a neutral area gradually increases as they get older (Adkins-Regan and Leung, 2006; Eliasson and Meyerson, 1981). In rats, the amount of approach behavior towards females stabilizes at an age when sexual hormones have reached their adult concentrations (Ojeda and Urbanski, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to mimic the physiological process of sexual maturation, testosterone replacement therapy was initiated approximately at the age at which the testes first start secreting high concentrations of androgens (Ottinger and Brinkley, 1979). Studies conducted in young rats and zebra finches revealed that the amount of time males spend looking at females as compared to males, family members or a neutral area gradually increases as they get older (Adkins-Regan and Leung, 2006; Eliasson and Meyerson, 1981). In rats, the amount of approach behavior towards females stabilizes at an age when sexual hormones have reached their adult concentrations (Ojeda and Urbanski, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, the amount of approach behavior towards females stabilizes at an age when sexual hormones have reached their adult concentrations (Ojeda and Urbanski, 1988). Interestingly, the magnitude of the preference for females appears to be altered by castration (Eliasson and Meyerson, 1981). In zebra finches, experimental manipulations of sex steroid hormones concentrations during the late juvenile development (prior to sexual maturation) resulted in a premature shift in the relative interest of males towards females as compared to family members (Adkins-Regan and Leung, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prepuberal or castrated males display no sexual approaches. 9,30,31 The same is the case with males that are sexually exhausted because of prolonged copulation, as mentioned earlier. 8 Only males in an appropriate state react to the sexualincentive stimuli emitted by the female.…”
Section: Sexual Attractionmentioning
confidence: 63%
“…Under some conditions, males do not approach sexually receptive females. Prepuberal or castrated males display no sexual approaches 9,30,31 . The same is the case with males that are sexually exhausted because of prolonged copulation, as mentioned earlier 8 .…”
Section: Sexual Attractionmentioning
confidence: 68%
“…Thus, older male voles may have more urine to contribute to producing overmarks than do younger male voles. Older adult male voles may be better than younger male voles at identifying the scent marks of sexually receptive female conspecifics, which allows older males to over-mark more of their over-marks (i.e., Eliasson & Meyerson 1981;Doty et al 1984;Mencio-Wszalek et al 1992). It is also possible that the accuracy with which an adult male deposits its scent marks on top of or near to those deposited by a female conspecific improves with age.…”
Section: Discussionmentioning
confidence: 99%